Taqwimu Manhaj Ta’lim Al Lughoh Al Arobiyah fil Madrosah Al Mutawasithoh Al Islamiyah Nurus Sunnah bi Semarang - Fajar Ledianto; Hafidah (Rayah Al-Islam, 2022)
ملخص البحث بذلت المدرسة المتوسطة الإسلامية نور السنة جهدا عظيما في محاولة تطوير منهج تعليم اللغة العربية من إحضارها المعلمين المتخصصين فيها لتفعيل التعليم، وإتيان الناطقين بها لتشجيع الطلبة على الرغبة الشديدة في تعلم اللغة العربية، ومن أهم أسس في تطوير منهج التعليم هو معرفة نتائج تقويمه حيث منه يؤخذ القرار في تعديل القديم الصالح ليصبح الجديد الأصلح. وأما الأهداف من كتابة هذا البحث هي لبيان وتوصيف : (1) منهج تعليم اللغة العربية في المدرسة المتوسطة الإسلامية نور السنة من حيث العوامل والعناصر. (2) تقويم منهج تعليم اللغة العربية في المدرسة من حيث العوامل والعناصر. (3) تحليل نتائج تقويم منهج تعليم اللغة العربية في المدرسة. هذا البحث هو البحث الوصفي التحليلي، وقوع هذا البحث في المدرسة المتوسطة الإسلامية نور السنة بسيمارانج. بدأ الباحث من شهر يوليو 2021 – نوفمبر 2021. الموضوع في هذا البحث هو رئيس المدرسة، ورئيس قسم اللغة العربية، ومدرسو اللغة العربية وعلومها، وبعض الطلاب والطالبات. أما طريقة جمع البيانات بالملاحظة والمقابلة والتوثيق. والاختبار في صدق البيانات باستخدام تثليث المصدر. ثم تحليلها بالنموذج التفاعلي ميليس وهيبرمان وهي تجميع البيانات، وتحديدها، وعرض البيانات المحصولة والمحدودة، ثم الاستنتاج. والنتائج المحصولة من هذه اللإجراءات هي أن : (1) العوامل المثيرة في تنفيذ منهج تعليم اللغة العربية في المدرسة هي عامل الطلبة والمعلم والمدرسة والإدارة. وأما عناصر منهج تعليم اللغة العربية في المدرسة يتضمن من الأهداف الثلاثة وهي أن يحصل الطلبة على الكفايات الثلاثة وهي الكفاية اللغوية والكفاية الاتصالية والكفاية الثقافية. (2) نتائج تقويم منهج تعليم اللغة العربية في المدرسة من حيث العوامل أنها تحتاج إلى توفير الناطقين باللغة العربية والمعمل اللغوي، ومن حيث العناصر فيها العوائق في محتوى كتب النحو حيث يصعب على الطلبة في استخدامه. (3 ) واستنتج الباحث بأن تقويم منهج تعليم اللغة العربية في هذه المدرسة شاملا وقيما حيث يجري جميع العوامل والعناصر من المنهج وفق أهداف منهج تعليم اللغة العربية في هذه المدرسة. ABSTRACT The Islamic junior high school Nurus Sunnah has made a great effort in trying to develop the Arabic language curriculum by bringing in specialized teachers to activate education, and to bring its speakers to encourage students to want to learn Arabic, and one of the most important foundations in the development of the curriculum is to know the results of its evaluation where the decision is taken to modify the old good to become the new fittest, The objectives of writing this research are to clarify and describe: (1)The curriculum of Arabic language teaching in the Islamic junior high school Nurus Sunnah terms of factors and elements. (2)Evaluating the Arabic language curriculum in the school in terms of factors and elements. (3)Analyzing the results of evaluating the Arabic language teaching curriculum in the school. This research is a qualitative descriptive research, and this research took place in the Islamic junior high school of Nurus Sunnah in Semarang. The researcher started from July 2021 - November 2021. The subject in this research is the head of the school, the head of the Arabic language department, the teachers of Arabic language and its sciences, and some male and female students. The method of data collection is observation, interview and documentation. And the test of data validity using source triangulation. Then analyze it using the interactive model Millis and Heberman, which is data collection, identification, display of the obtained and limited data, and then the conclusion.The results obtained from these procedures are that: (1) Exciting factors in implementing the Arabic language teaching curriculum in the school are the student factor, the teacher, the school and the administration. As for the elements of the Arabic language teaching curriculum in the school, it includes one of the three objectives, which is that the students obtain the three competencies, which are linguistic competency, communicative competency, and cultural competency. (2) The results of evaluating the Arabic language teaching curriculum in the school in terms of factors it needs to provide the speaker and the language lab, and in terms of the elements, they are hindrances in the content of grammar books, where it is difficult for students to use it. (3) The researcher concluded that the evaluation of the Arabic language curriculum in this school is comprehensive and valuable, as all factors and elements of education are conducted according to the objectives of the Arabic language curriculum in this school.